2015
DOI: 10.1111/ajt.13285
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Influenza A(H1N1) in a Kidney Transplant Unit—Protective Effect of Vaccination

Abstract: Seasonal influenza vaccination is recommended for patients with end‐stage renal disease (ESRD), despite suggested inferior efficacy among these patients. We characterize an outbreak of influenza A(H1N1) in a kidney transplant unit. Altogether 23 patients were treated on the ward for postoperative care after kidney transplantation during the outbreak. After the first positive case, all patients were tested with nasopharyngeal swab tests and 7 patients were diagnosed with influenza A(H1N1). Altogether 17/23 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…This may be related to the high frequency of cyclosporine use in our cohort, and the policy of using induction therapy only in immunologically high‐risk patients. Of note, three of the four patients who died due to Influenza A(H1N1) have been included in our previous description of an outbreak in our kidney transplant unit , showing a protective effect of pretransplant seasonal Influenza vaccination. In a recent study analysing deaths occurring during the first year after transplantation in a large cohort from United Kingdom , death within the first year after transplantation was reported in 3% of patients, most commonly from infectious or cardiovascular causes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the high frequency of cyclosporine use in our cohort, and the policy of using induction therapy only in immunologically high‐risk patients. Of note, three of the four patients who died due to Influenza A(H1N1) have been included in our previous description of an outbreak in our kidney transplant unit , showing a protective effect of pretransplant seasonal Influenza vaccination. In a recent study analysing deaths occurring during the first year after transplantation in a large cohort from United Kingdom , death within the first year after transplantation was reported in 3% of patients, most commonly from infectious or cardiovascular causes.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Nosocomial acquisition of influenza has been described as a risk factor for admission to ICU. 7,16 Use of influenza vaccination and early antiviral therapy has been consistently asso ciated with a reduced rate of influenzaassociated complications (pneumonia, admission to ICU, use of invasive ventilation, and death) 7,16,32,33 (see below).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…A randomized controlled trial in transplant recipients found that prophylaxis had ~80% efficacy. 44 In case of a close contact with a patient with documented influ enza, SOT recipients may receive postexposure prophylaxis with a oseltamivir, 45 particularly in case of high risk for complications (nos ocomial influenza early after transplant, 16 lung transplant recipients, or during therapy of rejection).…”
Section: Prevention/prophylaxismentioning
confidence: 99%
“…Data that providing masks for caregivers, visitors, and healthcare staff that interact closely with patients during respiratory virus season have been described by one center to decrease respiratory viruses in HCT recipients [68]. Influenza vaccination remains an important component of prevention every year and should be addressed through multimodal healthcare vaccine programs for patients, caregivers/ families and healthcare workers [69,70]. The appropriate length of isolation for patients with laboratory proven RVs is debated, as prolonged shedding is a common finding in these patients but viral load thresholds for infectivity are unknown.…”
Section: Respiratory Viral Preventionmentioning
confidence: 99%